Surgical Approach for Polycystic Ovarian Syndrome in Management of Infertility - Rath, SK (Med J Armed Forces India, 2006)
BACKGROUND: In patients with Polycystic Ovarian Syndrome (PCOS), resolution of infertility is an important goal of treatment. Wedge resection of the ovaries described as a means to achieve this was practiced in the middle of twentieth century. With the advent of endoscopic surgery, surgical approach for the same condition has been modified. Multi point biopsy, multiple needle puncture, electofulguration and laser fulguration are being tried in the context of PCOS. This project was taken up to evaluate the scope of electo fulguration in clomiphene resistant PCOS. METHODS: Forty patients who did not show sonographic evidence of ovulation with clomiphene citrate (CC) 100mg OD for 05 days in two cycles were subjected to laparoscopy. The patients who did not show any pelvic factor for infertility were alternately assigned to electro - fulguration treatment of ovaries or no fulguration during laparoscopy. These were designated as ‘Lap EC’ & ‘Only CC’ group respectively. For ‘Only CC’ group’ stimulation with CC was continued for four cycles with a higher dose 150 mg OD for 05 days. Lap EC group were subjected to CC 100mg OD for 5 days for two cycles in case of non achievement of ovulation in the first two drug free cycles following EC. Folliculometry, HCG administration and Intra Uterine Insemination (IUI) was performed for both groups. RESULTS: Total percentage of ovulatory cycles were 51.8% in EC group compared to 5.26% in the CC group. Overall pregnancy rate of 30% was achieved in the Lap EC group as compared to only 10% in the CC group (p<0.05). CONCLUSION: Laparoscopic electrofulguration of ovaries increases the chances of ovulation and conception. This being a cheaper one time procedure as compared to other expensive ovulation inducing agents, should be the preferred mode and the primary procedure wherever polycystic ovaries are encountered while evaluating a case of infertility by laparoscopy.